2005
DOI: 10.1007/s00213-005-2169-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GABAergic neuroactive steroid 3α-hydroxy-5α-pregnane-20-one as a neurobiological substrate for the anti-anxiety effect of ethanol in rats

Abstract: Our results demonstrated the contributory role of neuroactive steroid 3alpha, 5alpha-THP in the anti-anxiety effect of ethanol. It is speculated that ethanol-induced modulation of endogenous GABAergic neurosteroids, especially 3alpha, 5alpha-THP, might be crucial pertinent to the etiology of 'trait' anxiety (tension reduction) and ethanol abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 78 publications
(102 reference statements)
4
69
0
1
Order By: Relevance
“…Pre-treatment with finasteride (5α-reductase inhibitor) that reduces the synthesis of ALLO and THDOC, diminishes the subjective response to a moderate dose of alcohol in social drinkers (Pierucci-Lagha et al, 2005). Several studies in rodents have shown that ethanol-induced neuroactive steroids contribute to the acute behavioral effects of ethanol such as sedative-hypnotic (Van Doren et al, 2000;Khisti et al, 2003), anti-depressant (Hirani et al, 2002) and anxiolytic (Hirani et al, 2005). Moreover a relationship exists between the time course of ethanol-induced neurosteroids and specific behavioral and neural effects of ethanol ).…”
Section: Ethanol and Neurosteroidsmentioning
confidence: 99%
“…Pre-treatment with finasteride (5α-reductase inhibitor) that reduces the synthesis of ALLO and THDOC, diminishes the subjective response to a moderate dose of alcohol in social drinkers (Pierucci-Lagha et al, 2005). Several studies in rodents have shown that ethanol-induced neuroactive steroids contribute to the acute behavioral effects of ethanol such as sedative-hypnotic (Van Doren et al, 2000;Khisti et al, 2003), anti-depressant (Hirani et al, 2002) and anxiolytic (Hirani et al, 2005). Moreover a relationship exists between the time course of ethanol-induced neurosteroids and specific behavioral and neural effects of ethanol ).…”
Section: Ethanol and Neurosteroidsmentioning
confidence: 99%
“…ADX or inhibition of 5a-reduced steroid synthesis with the 5a-reductase (5a-R) inhibitor finasteride reduces some of the behavioral effects of ethanol, including the anticonvulsant (VanDoren et al, 2000), antidepressant-like (Hirani et al, 2002), and anxiolytic-like (Hirani et al, 2005) effects in rats. Finasteride also blocks ethanol inhibition of neuron firing in the medial septum (VanDoren et al, 2000), the hippocampus both in vivo (Tokunaga et al, 2003) and in vitro (Sanna et al, 2004), and long-term potentiation (LTP) in hippocampal slices (Tokuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…GABAergic neurons are one of the most important components prevalent in all areas of the brain and its neurotransmission is vital for brain function (5). Although GABA plays a major role in the modulation of virtually all cognitive and behavioural processes, several basic and clinical studies have particularly highlighted the role of this neurotransmitter in the central modulation of anxiety and stress responses (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%